Salmonella typhimurium synthesizes cobalamin (vitamin B12) de novo under anaerobic growth conditions. - Jeter, R M (1984)
In this paper, we report that the enteric bacterium Salmonella typhimurium synthesized cobalamin de novo under anaerobic culture conditions. Aerobically, metE mutants of S. typhimurium need either methionine or cobalamin as a nutritional supplement for growth. The growth response to cobalamin depends upon a cobalamin-requiring enzyme, encoded by the gene metH, that catalyzes the same reaction as the metE enzyme. Anaerobically, metE mutants grew without any nutritional supplements; the metH enzyme functioned under these conditions due to the endogenous biosynthesis of cobalamin. This conclusion was confirmed by using a radiochemical assay to measure cobalamin production. Insertion mutants defective in cobalamin biosynthesis (designated cob) were isolated in the three major branches of the cobalamin biosynthetic pathway. Type I mutations blocked the synthesis of cobinamide, type II mutations blocked the synthesis of 5,6-dimethylbenzimidazole, and type III mutations blocked the synthesis of cobalamin from cobinamide and 5,6-dimethylbanzimidazole. Mutants that did not synthesize siroheme (cysG) were blocked in cobalamin synthesis. Genetic mapping experiments showed that the cob mutations are clustered in the region of the S. typhimurium chromosome between supD (40 map units) and his (42 map units). The discovery that S. typhimurium synthesizes cobalamin de novo only under anaerobic conditions raises the possibility that anaerobically grown cells possess a variety of enzymes which are dependent upon cobalamin as a cofactor.